Preparation method and application of selenium nickel molybdenum sulfide catalyst

By preparing the selenium nickel sulfide catalyst, the problems of structural damage and irreversible loss of active sulfur during the fast charging and discharge process of lithium-sulfur batteries are solved, and the rapid charging and high energy density of lithium-sulfur batteries are achieved, which significantly improves its cycle life.

CN119390021APending Publication Date: 2025-02-07CENT SOUTH UNIV
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202411591682.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-08
Publication Date
2025-02-07

AI Technical Summary

Technical Problem

During the rapid charging and discharging process, lithium-sulfur batteries have problems such as structural damage, irreversible loss of active sulfur and insufficient conductivity, which affects their energy density and cycle life.

Method used

By preparing a selenium nickel sulfide molybdenum catalyst, the electronic structure of MoS2 is improved by using the doping of selenium and nickel, the active site is increased, and a catalyst with high conductivity and catalytic properties is obtained by hydrothermal reaction and annealing treatment.

Benefits of technology

It realizes fast charging and discharging of lithium-sulfur batteries under 20C conditions, with a charging time of only 1 minute, and significantly improved energy density and cycle life, which has better application prospects.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119390021A_ABST
    Figure CN119390021A_ABST
Patent Text Reader

Abstract

The invention discloses a preparation method and application of a selenium nickel molybdenum sulfide catalyst, and belongs to the technical field of energy materials, the preparation method comprises the following steps: adding selenium powder into a hydrazine hydrate solution to form a solution A; dissolving sodium molybdate dihydrate and thiourea in the reduced graphene oxide suspension to form a mixed solution B; mixing the solution A and the solution B together, stirring to obtain a solution C, transferring the solution C into a high-pressure kettle, and carrying out hydrothermal reaction to obtain a solution D; adding nickel acetate into the solution D, mixing and stirring, carrying out hydrothermal reaction again, washing with deionized water, and freeze-drying to obtain a black product A; and carrying out annealing treatment on the product A by using a tubular furnace under the protection of argon to obtain the selenium nickel molybdenum sulfide catalyst. According to the preparation method and application of the selenium nickel sulfide molybdenum catalyst, the conversion rate is remarkably increased, the interlayer spacing is enlarged, rapid movement of lithium ions is promoted, and the selenium nickel sulfide molybdenum catalyst has huge application potential in the field of rapid charging.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of energy materials, and in particular to a preparation method of a nickel-molybdenum-selenide sulfide catalyst and application thereof. Background Art

[0002] Fossil fuels are limited, and the use of large amounts of fossil fuels will cause environmental pollution and greenhouse effects. Cheap, clean, renewable energy is an important way to solve energy problems. However, renewable energy is affected by the natural environment and has strong uncertainty. It is necessary to redistribute and concentrate the generated electricity through energy storage devices, which is to "shaving the peak and filling the valley". In addition, in the application of mobile devices, such as electric vehicles, mobile computers, drones, smart phones, etc., energy storage devices determine the endurance and power limit. Energy storage equipment is the key to improving the utilization rate and application capabilities of renewable energy. Compare the mass energy density and power density of existing energy storage systems. Among them, lithium-ion batteries have considerable mass energy density, no memory effect, high open circuit voltage and other advantages, and have become the most important member of commercial energy storage devices. With the advancement of science and technology, higher requirements are placed on energy storage devices. Lithium-sulfur batteries (LSBs) have high energy density (2600Wh·kg -1 ), low cost and environmental friendliness, making it the most promising candidate for the next generation of batteries.

[0003] Lithium-sulfur batteries still face several challenges in their commercialization: (1) Sulfur has poor conductivity. During the discharge process, substances such as Li2S2 and Li2S are generated, which also have poor conductivity, affecting battery performance. (2) During the charge and discharge process of lithium-sulfur batteries, the large density difference between sulfur and Li2S causes a volume change of up to 80%, resulting in expansion and contraction that damages the structure. (3) Sulfur polysulfides generated during the discharge process that dissolve in the electrolyte migrate back and forth between the positive and negative electrodes, resulting in a shuttle effect that ultimately leads to irreversible loss of active sulfur and reduces battery life.

[0004] Molybdenum disulfide (MoS2) has attracted much attention due to its unique structure and catalytic properties. The layered structure formed by three S-Mo-S atoms through weak van der Waals forces provides abundant active sites, thereby improving the catalytic performance. Therefore, MoS2 shows great potential as a cathode electrode material for LSBs. However, current MoS2 materials face challenges such as poor ionic and electronic conductivity and insufficient catalytic activity, which hinder their ability to meet the high sulfur loading and fast charging requirements of LSBs. Summary of the invention

[0005] The purpose of the present invention is to provide a preparation method of a nickel molybdenum selenide sulfide catalyst and its application. The charging time is extremely short, and the battery can be fully charged in only 1 minute. The present invention has great potential in solving the problem of fast charging of batteries.

[0006] To achieve the above object, the present invention provides a method for preparing a nickel molybdenum selenide sulfide catalyst, comprising the following steps: S1, adding selenium powder to hydrazine hydrate solution to form solution A; S2, dissolving sodium molybdate dihydrate and thiourea in the reduced graphene oxide suspension to form a mixed solution B; S3, mixing solution A and solution B together and stirring to obtain solution C, and transferring solution C to an autoclave for hydrothermal reaction to obtain solution D; S4, adding nickel acetate to solution D, mixing and stirring, and then performing hydrothermal reaction again, then washing with deionized water, and freeze-drying after washing to obtain a black product A; S5. Performing annealing treatment on the product A in a tube furnace under argon protection to obtain a nickel molybdenum selenide sulfide catalyst.

[0007] Preferably, the temperature of mixing the selenium powder and the hydrazine hydrate solution in S1 is 50-100° C., the purity of the selenium powder is >99.99%, the particle size is <75 μm, and the purity of the hydrazine hydrate solution is analytical grade.

[0008] Preferably, the purity of sodium molybdate dihydrate in S2 is >99%, the purity of thiourea is >99.9%, and the concentration of reduced graphene oxide in solution B is 3-20 mg / mL.

[0009] Preferably, the stirring time in S3 is 0.25-3 h, and the stirring temperature is 40-80°C.

[0010] Preferably, the concentration of nickel acetate in solution D in S4 is 0.01-1 mmol / mL, the temperature of the hydrothermal reaction is 160-250° C., and the time is 10-30 h.

[0011] Preferably, the annealing temperature in S5 is 400-800° C., and the annealing time is 1-6 hours.

[0012] Preferably, the volume percentage content of hydrazine hydrate in solution C is 10-50%.

[0013] Preferably, the concentrations of selenium powder, sodium molybdate dihydrate and thiourea in solution C are all 2-8 mmol / mL.

[0014] Preferably, the mass percentage of nickel ions doped in the nickel molybdenum selenide sulfide catalyst is 1-10%.

[0015] The present invention also provides an application of a nickel-molybdenum-selenide sulfide catalyst, wherein the nickel-molybdenum-selenide sulfide catalyst prepared by the above-mentioned method for preparing a nickel-molybdenum-selenide sulfide catalyst is used as a positive electrode material in the preparation of a lithium-sulfur battery.

[0016] Therefore, the present invention adopts the above-mentioned preparation method of nickel molybdenum selenide sulfide catalyst and its application, which has the following beneficial effects: (1) The present invention introduces anion Se into MoS2 / rGO, which expands the interlayer spacing, enhances the intrinsic conductivity, and increases the ion diffusion rate. Subsequently, cation Ni is introduced to form an impurity energy level between the conduction band and the valence band. This modification leads to the rearrangement of the electronic structure of Mo, accelerates the redox reaction of polysulfides, and reduces its conversion energy barrier. Ultimately, it causes the d-band center to move upward, thereby reducing the occupancy of electrons in the antibonding orbital and accelerating the conversion of polysulfides. The synthesized catalyst has important practical application value in lithium-sulfur batteries.

[0017] (2) The preparation method of the present invention obtains a nickel molybdenum selenide sulfide catalyst grown on reduced graphene oxide through simple and mild solution treatment and hydrothermal reaction, and the surface has a large number of defects. The defect concentration and the nickel ion doping amount are controllable, and the defect concentration and the nickel ion doping amount can be controlled by adjusting the reaction time, temperature, nickel source dosage and other conditions.

[0018] (3) The nickel molybdenum selenide sulfide catalyst grown on reduced graphene oxide of the present invention, when prepared into a lithium-sulfur battery, has a higher energy density and a longer cycle life than a lithium-sulfur battery prepared with molybdenum disulfide. At 20C, the initial capacity is 641 mAh·g -1 The charging time is extremely short, and the battery can be fully charged in just 1 minute, which has better application prospects in solving the problem of fast battery charging.

[0019] (4) The nickel molybdenum selenide sulfide catalyst grown on reduced graphene oxide of the present invention can be rapidly charged and discharged at a current of 20C after being prepared into a lithium-sulfur battery, and the charging process can be completed in 1 minute, which has great application potential in the application scenario of fast charging.

[0020] (5) The preparation method of the nickel molybdenum selenide sulfide catalyst grown on reduced graphene oxide of the present invention is simple and easy to operate, and does not require complicated instruments and equipment. Nickel ions are used as dopants, which are inexpensive compared to catalyst materials containing precious metals and are suitable for industrial production. BRIEF DESCRIPTION OF THE DRAWINGS

[0021] The technical solution of the present invention is further described in detail below through the accompanying drawings and embodiments.

[0022] Figure 1 The X-ray diffraction (XRD) spectrum of the nickel molybdenum selenide sulfide catalyst grown on reduced graphene oxide prepared in Example 1 of the preparation method of the nickel molybdenum selenide sulfide catalyst of the present invention; Figure 2This is a transmission electron microscope (TEM) image of a nickel molybdenum selenide sulfide catalyst grown on reduced graphene oxide prepared in Example 1 of a method for preparing a nickel molybdenum selenide sulfide catalyst of the present invention and its application; Figure 3 This is a high-resolution transmission electron microscope (HRTEM) image of a nickel molybdenum selenide sulfide catalyst grown on reduced graphene oxide prepared in Example 1 of a method for preparing a nickel molybdenum selenide sulfide catalyst of the present invention and its application; Figure 4 This is a method for preparing a nickel molybdenum selenide sulfide catalyst of the present invention and its application Example 1. The constant current charge and discharge curve of the nickel molybdenum selenide sulfide catalyst grown on reduced graphene oxide prepared at a current of 20C. DETAILED DESCRIPTION

[0023] The technical solution of the present invention is further described below through the accompanying drawings and embodiments.

[0024] Unless otherwise defined, technical or scientific terms used in the present invention shall have the common meanings understood by one having ordinary skills in the field to which the present invention belongs.

[0025] The present invention provides a method for preparing a nickel-molybdenum-selenide sulfide catalyst, comprising the following steps: S1. Add selenium powder to hydrazine hydrate solution to form solution A. The mixing temperature of selenium powder and hydrazine hydrate solution is 50-100°C. The purity of selenium powder is >99.99%, the particle size is <75µm, and the purity of hydrazine hydrate solution is analytical grade.

[0026] S2. Dissolving sodium molybdate dihydrate and thiourea in the reduced graphene oxide suspension to form a mixed solution B, wherein the purity of sodium molybdate dihydrate is >99%, the purity of thiourea is >99.9%, and the concentration of reduced graphene oxide in solution B is 3-20 mg / mL.

[0027] S3, solution A and solution B are mixed together and stirred at 40-80° C. for 0.25-3 h to obtain solution C, and solution C is transferred to an autoclave for hydrothermal reaction to obtain solution D. The volume percentage content of hydrazine hydrate in solution C is 10-50%, and the concentrations of selenium powder, sodium molybdate dihydrate, and thiourea in solution C are all 2-8 mmol / mL.

[0028] S4, adding nickel acetate to solution D, mixing and stirring, and then performing hydrothermal reaction again, the temperature of the hydrothermal reaction is 160-250°C, and the time is 10-30 hours. Then washing with deionized water, and freeze-drying after washing to obtain a black product A, the concentration of nickel acetate in solution D is 0.01-1mmol / mL.

[0029] S5. Annealing the product A in a tubular furnace under argon protection at a temperature of 400-800° C. for 1-6 h to obtain a nickel molybdenum selenide sulfide catalyst, wherein the mass percentage of nickel ions doped in the nickel molybdenum selenide sulfide catalyst is 1-10%.

[0030] The present invention doped anion Se into MoS2 / rGO, and subsequently doped cation Ni to successfully prepare nickel molybdenum selenide sulfide. The introduction of nickel ions changes the semiconductor properties of MoS2 by introducing impurity energy levels between the conduction band and the valence band. This modification effectively reduces the band gap and increases the number of new active sites. These active sites actively participate in electron transfer during the transformation of polysulfides, and exhibit strong adsorption and catalytic abilities due to their high binding energy and low conversion energy barrier. On the other hand, the introduction of Se anions causes the Fermi level to move toward the conduction band, thereby increasing the intrinsic conductivity. In addition, it expands the interlayer spacing, promotes faster ion diffusion rates, and allows previously aggregated catalysts to be evenly dispersed on the surface of reduced graphene oxide (rGO). As a result, more active sites are exposed, leading to an overall improvement in catalytic performance.

[0031] Example 1 The invention provides a method for preparing a nickel molybdenum selenide sulfide catalyst, comprising the following steps: first, at 70°C, 0.75 mmol of selenium powder is added to 2.5 mL of hydrazine hydrate solution (98%) to form solution A. Then, 0.75 mmol of sodium molybdate dihydrate and 0.75 mmol of thiourea are dissolved in 10 mL of reduced graphene oxide suspension (10 mg / mL) to form a mixed solution B. Solution A and solution B are mixed and stirred for 15 minutes to obtain solution C. Solution C is transferred to a Teflon autoclave and stored at a temperature of 200°C for 24 hours to obtain a solution D. Subsequently, 0.1 mmol of nickel acetate is added to 10 ml of solution D, mixed and stirred, and then a hydrothermal reaction is performed again. Finally, the product is washed with deionized water and freeze-dried to obtain a black product A. Product A is annealed in a tubular furnace under the protection of argon gas and heated at 700°C for 2 hours to obtain a nickel molybdenum selenide sulfide catalyst grown on reduced graphene oxide.

[0032] Figure 1 The X-ray diffraction (XRD) spectrum of Example 1 is shown in the figure. Compared with the peaks of typical MoS2, the diffraction peaks before and after the introduction of Ni are similar, indicating that no new impurities are formed after the addition of Ni. After the introduction of selenium, the diffraction peak shifts to a lower diffraction angle. This shift is attributed to the lattice expansion caused by the replacement of some S atoms by larger Se atoms, and the increase in interlayer spacing.

[0033] Figure 2This is a transmission electron microscope (HRTEM) image of Example 1. As shown in the figure, the layered Ni-MoSSe nanosheets prepared in Example 1 grow uniformly on the redox graphene, and the average size is about 100 nm.

[0034] Figure 3 (a) is the transmission electron microscopy (HRTEM) image of Example 1, Figure 3 (b) Figure 3 (a) is a partial enlarged view. As shown in the figure, Ni-MoSSe nanosheets have the characteristics of a crystal structure. Figure 3 (c) is the brightness contour diagram of Ni-MoSSe / rGO, which provides information about the atomic distribution based on the peak width and peak spacing, indicating the distribution of atoms after the introduction of Ni and Se. The introduction of Ni and Se causes lattice distortion, increases active sites, and enhances the adsorption and catalytic performance of the catalyst.

[0035] Example 2 The invention provides a method for preparing a nickel molybdenum selenide sulfide catalyst, comprising the following steps: first, at 70°C, 0.75 mmol of selenium powder is added to 2.5 mL of hydrazine hydrate solution (98%) to form solution A. Then, 0.75 mmol of sodium molybdate dihydrate and 0.75 mmol of thiourea are dissolved in 10 mL of reduced graphene oxide suspension (10 mg / mL) to form a mixed solution B. Solution A and solution B are mixed and stirred for 15 minutes to obtain solution C. Solution C is transferred to a Teflon autoclave, stored at a temperature of 200°C for 24 hours, and a solution D is obtained by reaction. Subsequently, 0.01 mmol of nickel acetate is added to 10 ml of solution D, mixed and stirred, and then a hydrothermal reaction is performed again. Finally, the product is washed with deionized water and freeze-dried to obtain a black product A. Product A is annealed in a tubular furnace under the protection of argon gas, and heated at 800°C for 2 hours to obtain a nickel molybdenum selenide sulfide catalyst.

[0036] Example 3 The invention provides a method for preparing a nickel molybdenum selenide sulfide catalyst, comprising the following steps: first, at 70°C, 0.75 mmol of selenium powder is added to 2.5 mL of hydrazine hydrate solution (98%) to form solution A. Then, 0.75 mmol of sodium molybdate dihydrate and 1.5 mmol of thiourea are dissolved in 10 mL of reduced graphene oxide suspension (5 mg / mL) to form a mixed solution B. Solution A and solution B are mixed and stirred for 15 minutes to obtain solution C. Solution C is transferred to a Teflon autoclave, stored at a temperature of 220°C for 24 hours, and a solution D is obtained by reaction. Subsequently, 0.05 mmol of nickel acetate is added to 10 ml of solution D, mixed and stirred, and then a hydrothermal reaction is performed again. Finally, the product is washed with deionized water and freeze-dried to obtain a black product A. Product A is annealed in a tubular furnace under the protection of argon gas, and heated at 550°C for 2 hours to obtain a nickel molybdenum selenide sulfide catalyst.

[0037] Comparative Example 1 Compared with the preparation in Example 1, solution A is not required, and nickel acetate does not need to be added for secondary hydrothermal treatment. The remaining steps remain the same, thereby obtaining a molybdenum disulfide catalyst grown on reduced graphene oxide.

[0038] Comparative Example 2 Compared with the preparation in Example 1, solution A is not required, and the other steps remain the same, thereby obtaining a nickel-doped molybdenum disulfide catalyst grown on reduced graphene oxide.

[0039] Comparative Example 3 Compared with the preparation of nickel molybdenum selenide sulfide catalyst grown on reduced graphene oxide, there is no need to add nickel acetate for secondary hydrothermal treatment, and the other steps remain the same to obtain a molybdenum selenide sulfide catalyst grown on reduced graphene oxide.

[0040] In order to evaluate the effectiveness of Ni-MoSSe / rGO catalyst in actual lithium-sulfur batteries, sulfur was incorporated into the catalysts prepared in Comparative Examples 1, 2, 3 and Example 1 by conventional melt impregnation method to form a sulfur cathode and prepare a battery. The experimental steps are as follows: The synthesized catalyst is combined with sulfur by grinding and then heated in an inert atmosphere at 155 ° C for 12 hours. Subsequently, the active material (70%), polyvinylidene fluoride (PVDF, 10%) and carbon black (20%) were dissolved in N-methylpyrrolidone (NMP) to prepare a slurry. The slurry was then coated on aluminum foil and dried in a vacuum oven at 60 ° C for 12 hours. The dried coated foil was cut into sheets with a diameter of 10 mm. The cathodes synthesized in Comparative Examples 1, 2, 3 and Example 1 are S@MoS2 / rGO, S@Ni-MoS2 / rGO, S@MoSSe / rGO and S@Ni-MoSSe / rGO, respectively.

[0041] Figure 4 The performance diagram of the battery prepared with the material of Example 1 was subjected to a cycle test at 20C. After 500 cycles, the discharge capacity of the S@Ni-MoSSe / rGO-based battery prepared in Example 1 was 731 mAh·g -1 The capacity retention rate is 80.8%, exceeding that of S@MoSSe / rGO-based batteries (601mAh·g -1 , 71%), S@Ni-MoS2 / rGO-based batteries (607mAh·g -1 , 73.5%) and S@MoS2 / rGO-based batteries (583mAh·g -1 , 76.6%). This is due to the incorporation of selenium and nickel, which expands the interlayer spacing and facilitates the rapid insertion / extraction of lithium ions. In addition, the excellent conductivity and catalytic effect on polysulfides significantly accelerate the redox reaction in lithium-sulfur batteries.

[0042] Therefore, the present invention adopts the preparation method and application of the above-mentioned nickel molybdenum selenide sulfide catalyst, and introduces cations and anions into the MoS2 / rGO composite material at the same time, which will cause changes in the electronic structure of the catalyst, resulting in the upward shift of the d-band center and a decrease in the electron occupancy rate on the antibonding orbit. This modification effectively enhances the sulfur reduction reaction, and by changing the conversion pathway of polysulfides, its conversion rate can be significantly improved, the interlayer spacing is expanded, and the rapid movement of lithium ions is promoted, which has great application potential in the field of fast charging.

[0043] Finally, it should be noted that the above embodiments are only used to illustrate the technical solution of the present invention rather than to limit it. Although the present invention has been described in detail with reference to the preferred embodiments, those skilled in the art should understand that they can still modify or replace the technical solution of the present invention with equivalents, and these modifications or equivalent replacements cannot cause the modified technical solution to deviate from the spirit and scope of the technical solution of the present invention.

Claims

1. A method for preparing a nickel molybdenum selenide sulfide catalyst, characterized in that: The following steps are involved: S1, adding selenium powder to hydrazine hydrate solution to form solution A; S2, dissolving sodium molybdate dihydrate and thiourea in the reduced graphene oxide suspension to form a mixed solution B; S3, mixing solution A and solution B together and stirring to obtain solution C, and transferring solution C to an autoclave for hydrothermal reaction to obtain solution D; S4, adding nickel acetate to solution D, mixing and stirring, and then performing hydrothermal reaction again, then washing with deionized water, and freeze-drying after washing to obtain a black product A; S5. Performing annealing treatment on the product A in a tube furnace under argon protection to obtain a nickel molybdenum selenide sulfide catalyst.

2. The method for preparing a nickel molybdenum selenide sulfide catalyst according to claim 1, characterized in that: The temperature of the mixture of selenium powder and hydrazine hydrate solution in S1 is 50-100°C, the purity of selenium powder is >99.99%, the particle size is <75µm, and the purity of hydrazine hydrate solution is analytical grade.

3. The method for preparing a nickel molybdenum selenide sulfide catalyst according to claim 2, characterized in that: The purity of sodium molybdate dihydrate in S2 is >99%, the purity of thiourea is >99.9%, and the concentration of reduced graphene oxide in solution B is 3-20 mg / mL.

4. The method for preparing a nickel molybdenum selenide sulfide catalyst according to claim 3, characterized in that: The stirring time in S3 is 0.25-3h, and the stirring temperature is 40-80°C.

5. The method for preparing a nickel molybdenum selenide sulfide catalyst according to claim 4, characterized in that: The concentration of nickel acetate in solution D in S4 is 0.01-1 mmol / mL, the temperature of the hydrothermal reaction is 160-250° C., and the time is 10-30 h.

6. The method for preparing a nickel molybdenum selenide sulfide catalyst according to claim 5, characterized in that: In S5, the annealing temperature is 400-800°C and the annealing time is 1-6h.

7. The method for preparing a nickel molybdenum selenide sulfide catalyst according to claim 6, characterized in that: The volume percentage content of hydrazine hydrate in solution C is 10-50%.

8. The method for preparing a nickel molybdenum selenide sulfide catalyst according to claim 7, characterized in that: The concentrations of selenium powder, sodium molybdate dihydrate and thiourea in solution C are all 2-8 mmol / mL.

9. The method for preparing a nickel molybdenum selenide sulfide catalyst according to claim 8, characterized in that: The mass percentage of nickel ions doped in the nickel-molybdenum-selenide sulfide catalyst is 1-10%.

10. An application of a nickel molybdenum selenide sulfide catalyst, characterized in that: The nickel-molybdenum-selenide sulfide catalyst prepared by the method for preparing a nickel-molybdenum-selenide sulfide catalyst described in claim 9 is used as a positive electrode material in the preparation of a lithium-sulfur battery.

Citation Information

Patent Citations

  • Positive electrode / negative electrode material of lithium-sulfur battery and preparation method of positive electrode / negative electrode material

    CN114335468A

  • Preparation method of nickel-doped MoS2 / CoS2 / Ti3C2 composite material

    CN118581503A